Precision tomoghaphic system based on annular scintillation detector and Multi Pin-hole collimator - Dyomin, A.V.; Skibin, A.P. (Functional Materials, 2009)
Theoretical investigations have made it possible to derive an algorithm of 3-dimensional tomographic reconstruction for a cylindrical gamma-ray camera with a pin-hole type collimator. The optimum number of the pin-hole collimators has been found providing the image formation on the whole surface of the cylindrical detector. Formulas have been derived correlating the tomographic projections in the planar and cylindrical geometry. A precision tomographic system has been designed and constructed basing on an annular scintillation detector and a Multi Pin-hole collimator. The space resolution of the system amounts 1 mm.